Impact of Expenditures on Potable Water, Food Production, and Renewable Energy on Economic Growth and Sustainability in Saudi Arabia - Noureddine Kerrouche; Chokri Zehri (Journal of Sustainable Development of Energy, Water and Environment Systems)

(untitled)
Many countries have implemented significant reforms in industrial diversification within crucial sectors, impacting various areas. However, the full extent of these impacts remains empirically unclear. This study investigates the effects of Saudi government expenditures on potable water, food production, and renewable energy infrastructure on economic growth, social welfare, public health, and environmental sustainability. Using panel fixed-effects quarterly data from 2000 to 2023 analyzed through an Autoregressive Distributed Lag model. The study finds that potable water and food production expenditures significantly improve social welfare and public health. Specifically, water expenditure contributes to a 1.2% increase in social welfare and a 2.8% increase in public health. Food expenditure leads to a 0.8% improvement in social welfare and a 3.7% improvement in public health. Investment in renewable energy enhances economic growth, public health, and environmental sustainability. Additionally, combining investments in renewable energy with spending on potable water and food production further amplifies these positive effects. These findings underscore the need for the Saudi government to prioritize investments in potable water and renewable energy to boost health, welfare, and sustainability while also implementing targeted social programs.